Permasalahan perilaku sosial siswa di MTs Mamba'ul ‎Huda Banjarsari: Studi kasus di Desa Banjarsari ‎Kecamatan Ngajum Kabupaten Malang - Akbar, Yogi Muhammad (Maliki Interdisciplinary Journal, 2023)
The shift in social morality involving school students is still one of the nation's problems that is difficult to overcome. Not a few school students are involved in various forms of deviant social behavior, such as: speaking rudely and dirtily, low respect and courtesy, also committing violence among others. This is a sign of bad social morality among today's young generation. The purpose of this study is to find out what factors influence the morality of students at MTs Mamba'ul Huda which is located in Banjarsari Village, Ngajum District, Malang Regency. This research is qualitative research with the type of research used, namely the case study method. The data collection techniques used in this study were observation and interviews by going directly to the field to observe the behavior of MTs Mamba'ul Huda students and conducting interviews with informants to find out the causes that influence the social behavior of MTs Mamba'ul Huda students. The object of this study is the social behavior of some students at MTs Mamba'ul Huda with problems of social behavior both verbal and non-verbal. The results of the study show that there are several factors that influence students' social behavior problems at MTs Mamba'ul Huda. These factors include: gadgets, parenting patterns, family problems, and also social environmental factors.